Strandsvineblom Senecio pseudoarnica er en etablert art i Troms og en pestplante - Alm, Torbjørn (Norsk Botanisk Forening, 2020)
Journal home page at http://nhm2.uio.no/botanisk/nbf/blyttia/ . Senecio pseudoarnica was first reported from Norway in 2006, based on a surprise find at the outer-coast island of Sandøya in Tromsø, Troms. Originally interpreted as a case of long-distance dispersal from North America, it soon turned out that species had received human help in crossing the Atlantic. Seeds had been imported from Alaska to Balsfjord, Troms, by a garden enthusiast, who had shared the new ornamental with a number of other horticulturists. Four additional sites, also in Tromsø, were recorded in 2008, and left no doubt that this foreign introduction could escape from (or be thrown out of) gardens. Until recently, only a few further sites have been added, two in Tromsø (2015) and one in Nordreisa (2009), causing no alarm. A brief 2020 field work in Balsfjord revealed 42 occurrences distributed along 2.5 km of shoreline at Slettmo, comprising thousands of flowering stems. An additional search of 8 km shoreline further north yielded only a single plant near Laksvatn. The species is obviously invasive, naturalized in Norway, and already out of control.